Hyperthermia and radiotherapy: physiological basis for a synergistic effect - Righini, Michael F.; Durham, André; Tsoutsou, Pelagia G. (Frontiers in Oncology, 2024)
In cancer treatment, mild hyperthermia (HT) represents an old, but recently revived opportunity to increase the efficacy of radiotherapy (RT) without increasing side effects, thereby widening the therapeutic window. HT disrupts cellular homeostasis by acting on multiple targets, and its combination with RT produces synergistic antitumoral effects on specific pathophysiological mechanisms, associated to DNA damage and repair, hypoxia, stemness and immunostimulation. HT is furthermore associated to direct tumor cell kill, particularly in higher temperature levels. A phenomenon of temporary resistance to heat, known as thermotolerance, follows each HT session.HT is furthermore associated to direct tumor kill due to toxic shock but also thermotolerance. Cancer treatment requires innovative concepts and combinations to be tested but, for a meaningful development of clinical trials, the understanding of the underlying mechanisms of the tested modalities is essential. In this mini-review, we aimed to describe the synergistic effects of the combination of HT with RT as well as the phenomena of thermal shock and thermotolerance, in order to stimulate clinicians in new, clinically relevant concepts and combinations, which become particularly relevant in the era of technological advents in both modalities but also cancer immunotherapy.